Pengaruh Penilaian Terhadap Audit Quality: Insentif Kerja, Pengalaman Auditor Dan Kompleksitas Tugas - Nabila Imanina Fahira; Cris Kuntad; Afina Azzahra (STIKes Ibnu Sina Ajibarang, 2024)
The aim of this research is to examine the factors that influence intensive assessment, auditor experience and task complexity on audit quality. This research aims to analyze the influence of intensive assessment, auditor experience, and task complexity on audit quality. This research uses quantitative methods with multiple linear regression techniques. Research data was obtained from 100 auditors working at KAP in Indonesia. The research results show that intensive assessment, auditor experience, and task complexity have a significant influence on audit quality. Intensive assessment and auditor experience have a positive influence on audit quality, while task complexity has a negative influence on audit quality.